2010
DOI: 10.1002/nau.20907
|View full text |Cite
|
Sign up to set email alerts
|

Mixed incontinence: Current evidence and future perspectives

Abstract: The epidemiology and treatment of mixed incontinence has received relatively little attention. However, mixed incontinence--defined as the combination of stress and urge incontinence accounts for approximately 33% of all cases of incontinence in women. The condition often responds poorly to treatment, either pharmacologic or surgical. Potential pharmacologic approaches for mixed incontinence include antimuscarinic agents, estrogen replacement therapy (for postmenopausal women), and dopamine, serotonin, or nore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 44 publications
0
31
0
1
Order By: Relevance
“…MUI was also the most common clinical diagnosis in studies conducted in older populations 3,4 . In addition, women seen at other Brazilian referral centers have been diagnosed with MUI more frequently 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MUI was also the most common clinical diagnosis in studies conducted in older populations 3,4 . In addition, women seen at other Brazilian referral centers have been diagnosed with MUI more frequently 20 .…”
Section: Discussionmentioning
confidence: 99%
“…European epidemiological studies have shown that, based on each clinical category, 50% of all women with UI are classified as having stress urinary incontinence (SUI), followed by mixed urinary incontinence (MUI) and overactive bladder (OB) 2 . The prevalence of these subtypes varies with age, and older women show a higher prevalence of MUI [2][3][4] . Several factors related to the increasing prevalence of UI, such as age and parity, have already been cited in the literature at length 5,6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators, however, often have grouped several different pathologies together under the category of ''mixed incontinence.'' (Khullar et al, 2010) Further compounding the definition of MUI is an acknowledged fact that stress incontinence may also be misperceived as an urgency event. The presence of urine in the posterior urethra may actually induce urinary urgency and eventuate in a secondary episode of detrusor overactivity (stress-induced detrusor overactivity).…”
Section: Prevalence Of Muimentioning
confidence: 99%
“…Potential pharmacologic approaches to the treatment of mixed incontinence include antimuscarinic agents, estrogen replacement therapy (for postmenopausal women), and dopamine, serotonin, and norepinephrine reuptake inhibitors. (Khullar et al, 2010) Electrical stimulation is another conservative measure that could potentially be used for the treatment of MUI. (Sand, 1996) Surgery should be considered after failed medical management, proper work up, and careful counselling about the lower overall success rates of around 55%.…”
Section: Outcome Of Midurethral Sling In Resolution Of Mixed Urinary mentioning
confidence: 99%